PERTANGGUNG JAWABAN PELAKU USAHA ATAS TINDAKAN PERBUATAN CURANG YANG MERUGIKAN HAK HAK KONSUMEN - Herry Anto Simanjuntak (JURNAL JUSTIQA, 2022)
Along with the progress of the times followed by the development of the economy in general, especially in the field of industry and national trade, it has produced various variations of goods and/or services that can be consumed. In addition, globalization and free trade are supported by advances in telecommunications and information technology which have expanded the space for the flow of transactions of goods and services across the borders of a country, so that the goods/services offered vary both domestically and abroad. This situation becomes a positive or negative challenge, where a positive challenge can provide benefits for consumption, being able to freely choose the goods/or services they want where consumers have the freedom to determine the type and quality of goods/services according to their needs. Furthermore, from the negative side where these conditions cause the position of consumers to be weaker than business actors.Whereas, considering such conditions, on the one hand, it has benefits for the condition of consumers because consumer needs for the desired goods and/or services can be fulfilled and freedom is wide open to choose various types and quality of goods and/or services in accordance with the wishes and abilities of consumers. Meanwhile, on the other hand, the phenomenon mentioned above can result in the position of business actors and consumers being unbalanced, where the position of consumers becomes the object of business activity to reap the greatest profit with economic principles. Making consumers the object of business activity to reap as much profit as possible by business actors will lead to competition between business actors themselves, this will change the behavior of business actors towards unfair business competition. Unfair competition by business actors includes promotional tips, sales methods, and the application of standard agreements that can harm consumers, which can lead to disputes between consumers and business actors. This dispute can be in the form of one of the parties not getting or not enjoying what they should be entitled to because the other party does not fulfill its obligations.